THE IMPACT OF THE COVID-19 PANDEMIC ON THE FULFILLMENT OF CREDIT WITH MORTGAGE RIGHTS IN LEGAL TERMS FOR THE DEBTOR - Adella Rachma Juliani; Siti Malikhatun Badriyah (Awang Long Law Review, 2023)
The Covid-19 has an impact that affects many sectors, including the implementation of credit agreements that are subject to dependent rights. These effects led the debtor to experience overmacht and force majeure, so it is difficult to fulfill the obligations from the contract because income during the CoAvid-19 pandemic was unstable. The approach used in this study is normative juridical. The results showed that the situation of the Covid-19 pandemic can be used as a basis for overmacht because it has fulfilled the elements of overmacht. Thus, the execution of the debtor's liability rights object is not possible, which is hindered by the fulfillment of its credit obligations. Issuance of POJK Number 11/POJK.03/2020 on National Economic Stimulus as a Countercyclical Policy on the Impact of Coronavirus Disease 2019 as a policy that provides legal protection for overmacht debtors affected by Covid-19 by providing credit restructuring.